A study of wetland hydrology and ecosystem service provision: GaMampa wetland, South Africa - McCartney, Matthew P.; Morardet, S.; Rebelo, Lisa-Maria; Finlayson, C. Max; Masiyandima, Mutsa (Informa UK Limited, 2011)
The GaMampa wetland, a palustrine wetland, comprises less than 1% of the catchment but is widely believed to make a significant contribution to dry-season river flow in the Mohlapitsi River, a tributary of the Olifants River, in South Africa. The contribution of the GaMampa wetland to dry-season flow in the Mohlapitsi River and the impact of increasing agriculture on its hydrological functioning were investigated. Economic analyses showed that the net financial value of the wetland was US$ 83,263 of which agriculture comprises 38%. Hydrological analyses indicated that the Mohlapitsi River contributes, on average, 16% of the dry-season flow in the Olifants River. However, the wetland contributes, at most, 12% to the increase in dry-season flow observed over the reach of the river in which the wetland is located. The remainder of the increase originates from groundwater flowing through the wetland. Furthermore, despite the conversion of 50% of the wetland to agriculture since 2001, there has been no statistically significant reduction in dry-season flow in the Mohlapitsi River. These results highlight the importance of understanding the nature of the full suite of services being provided by a wetland in order to make informed decisions for appropriate management.